Dichromated gelatine as a material of optical element - Lee, Hyuk-Soo; Cho, Dong-Hyun; Choi, Yong-Jin; Son, Jung-Young; Seung-Han, P (JAPAN J APPLIED PHYSICS, 1999)
In the fabrication process of optical elements (OEs) by the laser scanning method using a dichromated gelatin (DCG) photoplate, the expansion and drying stress of gelatine caused by inhomogeneous liquid flow inside the gelatine affects the shape of OEs. The reason this inhomogeneous liquid flow exists in the energy oversaturated parts of OEs is the presence of surplus energy. In order to obtain the OEs of desired spherical lens shape, the drying stress should be reduced and therefore the maximum energy of the illuminating laser should be defined not to cause the surplus energy. The maximum energy is investigated according to the relative concentrations of(NH4)(2)Cr2O7 to DCG. The use of photoplates with a relative concentration of (NH4)(2)Cr2O7 to gelatin of more than 20% has some advantages when making the lens raster, especially a short-focal-length lens raster. It is also very important to increase the drying time to reduce the total drying stress by maintaining high humidity during the drying process.